Balanced Crystalloid Versus Normal Saline as Resuscitative Fluid in Diabetic Ketoacidosis. Issue 9 (September 2022) - Carrillo, Adriana R.; Elwood, Kirsten; Werth, Chris; Mitchell, Jessica; Sarangarm, Preeyaporn
Background: Large volume resuscitation with normal saline (NS) may be associated with iatrogenic hyperchloremia and renal injury. Objective: The purpose of this study was to assess clinical outcomes associated with the use of Lactated Ringer's (LR) compared to NS as resuscitative fluid in diabetic ketoacidosis (DKA). Methods: Single-center, retrospective analysis of patients admitted for DKA. The primary objective of this study was to evaluate the incidence of iatrogenic hyperchloremia associated with fluid resuscitation using balanced crystalloid compared to NS. Results: Iatrogenic hyperchloremia occurred more frequently in the NS group compared to the LR group (74.4% vs 64.2%; P = 0.05). Mean maximum serum chloride was higher in the NS group (115.7 mmol/L vs 113.7 mmol/L; P = 0.004). Incidence of hypernatremia was higher in the NS group (18.3% vs 9.3%; P = 0.02). There was no significant difference in the incidence of AKI; however, mean change in serum creatinine at 48 hours showed a significantly greater decrease in the LR group (-0.15 mg/dL vs -0.04 mg/dL; P = 0.002). No significant differences were found in intensive care unit (ICU) length of stay or total hospital length of stay. Conclusion and Relevance: This study found a statistically significant reduction in the incidence of iatrogenic hyperchloremia with the use of LR compared to NS as fluid resuscitation in DKA. Serum creatinine was more improved in the LR group versus NS group at 48 hours. Preferential use of balanced crystalloid for fluid resuscitation in DKA may reduce incidence of hyperchloremia and support renal recovery in this population.